FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA UPT PUSKESMAS PASAR KEPAHIANG - Regita Maheswari; Ramon, Agus; Husin, Hasan; Wati, Nopia (Avicenna: Jurnal Ilmiah, 2024)
Background : The infectious disease known as bacterial tuberculosis (TB) mainly affects the lungs, leading to respiratory problems like coughing and breathing problems. The study's focus was on instances of pulmonary tuberculosis (TB) at UPT Pasar Kepahiang Health Center's Working Area. Method : The research used a quantitative approach with observational methods, and for univariate analysis it used frequency distribution tables; for bivariate analysis, it used the Chi-Square test. Results :  It was shown that the majority of knowledge factors were in the poor category (46 people or 76.7%), the majority of attitude factors were in the negative category (45 people or 75.0%), the majority of behavioral factors were in the good category (31 people or 35.0%), and the majority of pulmonary tuberculosis cases were in the category of Passive TB (37 people or 61.7%). The results of the investigation showed a significant correlation (p-value 0.001<0.05) between TB knowledge and TB incidence in the Kepahiang Health Center's Working Area. In the same region, attitudes and tuberculosis incidence was significantly correlated (p-value 0.021<0.05). And there is a clear connection (p-value 0.013 0.05) between conduct and the incidence of tuberculosis. Conclusion : In conclusion, the incidence of pulmonary tuberculosis in the Working Area of UPT Pasar Kepahiang Health Center is significantly correlated with knowledge, attitudes, and actions..   Keywords : Disease, Lung, Tuberculosis